Effect of resistance exercises (burdeners) in development Achievement level (022) m (Journal of the College of Basic Education, 2023)
The importance of research by using weights in speed training, one of which is effective (100 m), whichrequire a degree of speed that needs to develop strength and a percentage of endurance; So it was usedAs one of the training tools for runners, it takes up space from the training units in a way that is compatible with itIt conflicts with the vocabulary of the training unit in order to be a catalyst in developing some traitsFor runners, and the research problem is in developing college runners and their times by this means, as the researcher saw fromWeakness in their achievement and because of reliance on traditional methods of developing strength and improving strengthAs a result, it leads to an improvement in the speed of completion. The study aimed to know the effect of using weightson the runners of the College of Arts team in the event of running (100 m), and I assumed that there are significant differencesStatistics between the two tests (pre and post) and in favor of the post test in running (002) m;For the selected runners of the Faculty of Arts, the researcher used the semi-arbitrary experimental method of this groupthe one; The research sample included (5) elected runners from the College of Arts / University of Baghdad, for an event(100) AD; for the academic year (4102/2013), representing the research community by (100%). As for the meansThe statistics are: the arithmetic mean; the mediator. standard deviation Torsion Modulus»» Test(7)For associated samples, I concluded that the use of this type of training is suitable for runners at the beginningPhase special preparation recommended using this type of weights for other parts of the bodyLike the arms to develop the swing, in addition to other types of weights, such as the sand weighted chest.